Through fiery trials [compact disc, unabridged] - Weber, David, 1952- (Weber, David, 1952- Safehold series., 2019)
Those on the side of progressing humanity through advanced technology have finally triumphed over their oppressors.The unholy war between the small but mighty island realm of Charis and the radical, luddite Church of God's Awaiting has finally come to an end. However, even though a provisional veil of peace has fallen over human colonies, many secrets of Safehold's past still remain unearthed. With new alliances forged and old regimes fractured, Merlin--the cybernetic avatar of Earth's last survivor and immortal beacon to humanity--and the colonies of Safehold have many adventures ahead in the continuation of David Weber's New York Times bestselling Safehold series.